Production of aerobactin by some species of the genus Yersinia. - Stuart, S J (1986)
Seventy-seven isolates of Yersinia species were examined for evidence of hydroxamate biosynthesis. A total of 7 of 12 Y. frederiksenii, 1 of 5 Y. kristensenii, and 5 of 5 Y. intermedia isolates synthesized an hydroxamate species which was chromatographically and electrophoretically identical to aerobactin. Proof that this material was indeed aerobactin was obtained for one strain of Y. frederiksenii by using mass spectrometry. None of 50 Y. enterocolitica nor any of 5 Y. pseudotuberculosis isolates produced hydroxamates.